Autonomic testing for prediction of competition performance in Paralympic athletes. (22nd May 2017) - Squair, J. W.; Phillips, A. A.; Currie, K. D.; Gee, C.; Krassioukov, A. V.
Abstract : While we now appreciate that autonomic dysfunction can impact wheelchair rugby performance, this is currently not being assessed during classification, largely due to lack of a standardized and evidence‐based strategy to assess autonomic function. Our aim, therefore, was to establish the optimal autonomic testing protocol that best predicts cardiovascular capacity during competition by comprehensively examining autonomic function in elite wheelchair rugby athletes with cervical SCI and thereby enhance the standardized classification. Twenty‐six individuals with cervical SCI (C4‐C8; AIS A, B, C) participated in this study during the 2015 Parapan American Games in Toronto, Canada. Clinic autonomic testing included: sympathetic skin responses, baseline hemodynamics, orthostatic challenge test, and cold‐pressor tests. Further, we completed standard motor/sensory assessments and obtained each participants' International Wheelchair Rugby Federation classification. These clinic metrics were correlated to in‐competition heart rate monitoring obtained during competition. The current study provides novel evidence that the change in systolic blood pressure during an orthostatic challenge test predicts approximately 50% of the in‐competition peak heart rate ( P <.001). Conversely, International Wheelchair Rugby Federation classification was poorly associated with in‐competition peak heart rate ( R 2 =.204; P <.05). Autonomic testing provides deep insight regarding preserved autonomic control after SCI that is associated with performance in elite wheelchair rugby athletes. As such, incorporating assessments of cardiovascular capacity in classification will help to ensure a level playing field and may obviate the need for practices such as boosting to gain an advantage due to poor cardiovascular control.